Students' Satisfaction Towards the Use of E-learning during the Global Pandemic - Fozeli, Aina Dayana; Sani, Norarnitasha Abdullah; Mustafa, Ainin Sofiya; Khalid, Nur Afifah; Chawla, Pooja (AIBPM Publisher, 2022)
During the global pandemic, e-learning became even more popular and used by many educational institutions worldwide to facilitate the students' learning process. Students can easily get the related materials and resources from e-learning. This research intends to examine the level of students' satisfaction with e-learning and their learning experiences during the global pandemic. The quantitative research method was carried out using a questionnaire survey and online research. 150 students from different institutions in India and Malaysia have participated in the survey. The survey was carried out through Google Form and the data were exported to be analyzed using SPSS. The results showed that most of the students were satisfied with e-learning and how e-learning helped them in their studies. The results of this study indicated that convenience flexibility was significantly related to students’ learning experiences.